2020
DOI: 10.3389/fcell.2020.583919
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Intestinal Stem Cells Induced by Acute and Chronic Injury: The Saving Grace of the Epithelium?

Abstract: The intestinal epithelium is replenished every 3–4 days through an orderly process that maintains important secretory and absorptive functions while preserving a continuous mucosal barrier. Intestinal epithelial cells (IECs) derive from a stable population of intestinal stem cells (ISCs) that reside in the basal crypts. When intestinal injury reaches the crypts and damages IECs, a mechanism to replace them is needed. Recent research has highlighted the existence of distinct populations of acute and chronic dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 125 publications
(169 reference statements)
2
34
0
Order By: Relevance
“…46 Previously, intestinal epithelial repair was studied after acute injury after ablation of LGR5þ ISCs by irradiation, chemotherapeutic agents, or diphtheria toxin. 34,[47][48][49][50] When active ISCs are selectively lost in acute injury models, reserve ISCs become activated and converted to active ISCs. The epithelial repair is completed as the active ISC pool is replenished by reserve ISCs and all epithelial cell types are regenerated.…”
Section: Discussionmentioning
confidence: 99%
“…46 Previously, intestinal epithelial repair was studied after acute injury after ablation of LGR5þ ISCs by irradiation, chemotherapeutic agents, or diphtheria toxin. 34,[47][48][49][50] When active ISCs are selectively lost in acute injury models, reserve ISCs become activated and converted to active ISCs. The epithelial repair is completed as the active ISC pool is replenished by reserve ISCs and all epithelial cell types are regenerated.…”
Section: Discussionmentioning
confidence: 99%
“…The cells at the +4 position have a unique transcriptional profile, which includes the expression of HOPX [ 26 , 27 ]. These +4 cells have previously been described as part of the resting stem cell population, which rebuilds Lgr5+ CBCs upon injury and has been found to be radiation resistant, implying that they can survive crypt injury and replace their damaged counterparts [ 28 ]. Furthermore, HOPX-positive intestinal stem cells in the +4 locations are resistant to anoikis, a type of apoptosis caused by aberrant cell matrix connections [ 29 ].…”
Section: Hopx In Development and Differentiationmentioning
confidence: 99%
“…An area of considerable interest in gastrointestinal biology is the link between epithelial differentiation and regeneration 21,114,115 . Although it was long thought that dedicated "reserve" stem cells at the +4/+5 region, marked by expression of genes such as Bmi1 and mTert, replenished the stem cell compartment in intestinal epithelial regeneration, recent data have indicated that these cells are most likely enteroendocrine cells with the ability to de-differentiate into stem cells following injury 8,22 .…”
Section: Discussionmentioning
confidence: 99%